“Comfort Zone” of Counselor and Counselee in Counseling Service - Pratiwi, Awalya Siska; Setiyowati, Arbin Janu (Ma'soem University, 2025)
The provision of guidance and counseling services with the aim of achieving optimal student development will be implemented if the counselor knows what factors make the counselee feel comfortable. The objective of this study is to assess the level of comfort experienced by both the counselor and the counselee, thereby facilitating the realization of the service. The research employed is a qualitative literature review, examining several sources, including books, journals, and other relevant materials, as the primary research object. It has been determined that becoming a counselor is not solely contingent upon physical evidence, such as a diploma that substantiates completion of a bachelor's degree program in guidance and counseling, along with graduation from a professional education program for teachers. Additional factors must be taken into consideration. A professional counselor must possess a fundamental understanding of the ethical principles that govern their practice and exhibit personal characteristics conducive to effective counseling. When a counselor exhibits the anticipated characteristics and ethics, establishing a relationship between the counselor and the counselee is not a sufficient challenge in itself. In addition to the internal factors present within a counseling context, external factors such as facilities and infrastructure play a pivotal role in the implementation of counseling services.